ATF3 Regulates Osteogenic Function by Mediating Osteoblast Ferroptosis in Type 2 Diabetic Osteoporosis. (26th October 2022) - Zhao, Yantao; Du, Yunxia; Gao, Yijie; Xu, Zhijie; Zhao, Dexiang; Yang, Maowei
Abstract : Purpose . Osteoporosis is a complication of type 2 diabetes, and it is characterized by reduced bone mass, augmented bone fragility, and increased risk of fracture, thus reducing patient quality of life, especially in the elderly. Ferroptosis has been implicated in the pathological process of type 2 diabetic osteoporosis (T2DOP), but the specific underlying mechanisms remain largely unknown. This study clarified the role of activating transcription factor 3 (ATF3) in T2DOP and explored its specific regulatory mechanism, providing a new treatment target for T2DOP. Methods . We cultured hFob1.19 cells in high glucose (HG, 35 mM) and knocked down ATF3 using short hairpin RNA (shRNA). We then measured cell viability, assessed morphology, quantified the expression of ATF3 and glutathione peroxidase 4 (GPX4), detected the levels of reactive oxygen species (ROS) and lipid peroxides, and determined the osteogenic function of osteoblasts. Cystine/glutamate antiporter (system Xc - ) activity was evaluated by determining the expression of SLC7A11 and the levels of glutathione (GSH) and extracellular glutamate. We constructed a T2DOP rat model and observed the effect of ATF3 on ferroptosis and T2DOP by knocking down ATF3 using small interfering RNA (siRNA). Then, we evaluated the levels of iron metabolism, lipid peroxidation, and bone turnover in serum, detected the expression of ATF3, SLC7A11, and GPX4 in bone tissues, and assessed bone microstructure using microcomputed tomography. Results . ATF3 expression was increased in osteoblasts under HG condition and in T2DOP rats. Inhibiting the function of ATF3 increased GPX4 levels and reduced the accumulation of ROS and lipid peroxides. These changes inhibited the ferroptosis of osteoblasts and improved osteogenic function. In addition, HG induced ATF3 upregulation, resulting in decreased SLC7A11 expression and lower levels of intracellular GSH and extracellular glutamate. Conclusion . Osteoblast ferroptosis under HG conditions is induced by ATF3-mediated inhibition of system Xc - activity, and these events contribute to T2DOP pathogenesis.